Crowdfunding FOR MEDICAL CARE: Ethical Issues in an Emerging Health Care Funding Practice - Snyder, Jeremy (The Hastings Center report, 2016)
Crowdfunding websites allow users to post a public appeal for funding for a range of activities, including adoption, travel, research, participation in sports, and many others. One common form of crowdfunding is for expenses related to medical care. Medical crowdfunding appeals serve as a means of addressing gaps in medical and employment insurance, both in countries without universal health insurance, like the United States, and countries with universal coverage limited to essential medical needs, like Canada. For example, as of 2012, the website Gofundme had been used to raise a total of 8.8 million dollars (U.S.) for seventy-six hundred campaigns, the majority of which were health related. This money can make an important difference in the lives of crowdfunding users, as the costs of unexpected or uninsured medical needs can be staggering. In this article, I offer an overview of the benefits of medical crowdfunding websites and the ethical concerns they raise. I argue that medical crowdfunding is a symptom and cause of, rather than a solution to, health system injustices and that policy-makers should work to address the injustices motivating the use of crowdfunding sites for essential medical services. Despite the sites’ ethical problems, individual users and donors need not refrain from using them, but they bear a political responsibility to address the inequities encouraged by these sites. I conclude by suggesting some responses to these concerns and future directions for research.